#### Answer

$-r = t-s$

#### Work Step by Step

We use the equation for slope:
$m = \frac{y_2-y_1}{x_2-x_1}$
We set the two slopes equal to each other, for they are parallel:
$ \frac{v}{-r} = \frac{v}{t-s} \\ \frac{1}{-r} = \frac{1}{t-s} \\ -r = t-s$

Published by
Brooks Cole

ISBN 10:

ISBN 13:

$-r = t-s$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.